Retrospective analysis of Smoking Habits and Height of Residual Bone on Implant Survival and Success Rate in Lateral Sinus Lift - Dhole, Rohit; Bhattacharjee, Swarnika; Sharma, Neha; Lahoti, Kapil; Singh, Nilanshu; Makkad, Ramanpal Singh (Journal of Neonatal Surgery, 2025)
Background: Dental implant placement in the posterior maxilla often requires lateral sinus lift procedures due to insufficient bone height. Several factors, including smoking habits and residual bone height, may influence the survival and success rate of implants in such cases. This retrospective study aims to analyze the effects of smoking and residual bone height on the success and survival rates of implants placed with lateral sinus lift augmentation. Materials and Methods: A retrospective analysis was conducted by reviewing the records of 100 patients (60 males, 40 females; age range: 30–65 years) who underwent lateral sinus lift procedures with implant placement from 2015 to 2022. Patients were divided into two groups based on smoking status (Smokers: 50; Non-Smokers: 50) and residual bone height categories (Low: ≤4 mm, Moderate: >4 mm to ≤6 mm, High: >6 mm). A total of 200 implants were evaluated for survival and success rates at follow-ups of 6 months, 1 year, and 3 years. Success was determined based on clinical and radiographic parameters, including absence of mobility, pain, and radiolucency. Results: The overall implant survival rate was 92%, while the success rate was 85%. In smokers, the survival rate was 88%, and the success rate was 80%. In non-smokers, the survival rate was 96%, and the success rate was 90%. Patients with low residual bone height had a success rate of 78%, while those with moderate and high bone height had success rates of 87% and 91%, respectively. Statistically significant differences (p < 0.05) were noted between smokers and non-smokers, as well as among different bone height categories. Conclusion: Smoking habits and residual bone height significantly affect the survival and success rates of implants placed with lateral sinus lift augmentation. Non-smokers and patients with greater residual bone height demonstrated higher implant success and survival rates. Careful assessment of these factors is essential for predictable outcomes in sinus lift procedures.